2002
DOI: 10.1159/000063627
|View full text |Cite
|
Sign up to set email alerts
|

High Concentrations of Soluble Fas Ligand in Bronchoalveolar Lavage Fluid of Patients with Pulmonary Sarcoidosis

Abstract: Background and Objectives: Sarcoidosis is a systematic granulomatous disorder of unknown origin characterized by accumulation of T lymphocytes and macrophages in multiple organs. We postulated that apoptosis through the Fas/Fas ligand (L) system may be associated with regulation of immune reactions characterized by the formation of noncaseous necrotizing granulomas. Soluble (s) FasL is not equivalent to membrane-associated FasL since conversion of membrane-bound FasL to the soluble form is associated with down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…In fact, the presence of elevated levels of the anti-apoptotic protein soluble Fas in the serum and its message in peripheral blood mononuclear cells from silicosis patients (Otsuki et al, 2000) indicates that the granuloma formation in human silicosis may not be associated with apoptotic cell death. The presence of anti-apoptotic factors, including soluble Fas and soluble Fas ligand, was also found in other fibrotic/granulomatous human lung diseases, including tuberculosis, sarcoidosis, and pulmonary fibrosis (Kuwano et al, 2000; Ordway et al, 2005; Shikuwa et al, 2002). Moreover, the results from other proliferative diseases suggest that apoptosis is associated with improvement in the disease.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, the presence of elevated levels of the anti-apoptotic protein soluble Fas in the serum and its message in peripheral blood mononuclear cells from silicosis patients (Otsuki et al, 2000) indicates that the granuloma formation in human silicosis may not be associated with apoptotic cell death. The presence of anti-apoptotic factors, including soluble Fas and soluble Fas ligand, was also found in other fibrotic/granulomatous human lung diseases, including tuberculosis, sarcoidosis, and pulmonary fibrosis (Kuwano et al, 2000; Ordway et al, 2005; Shikuwa et al, 2002). Moreover, the results from other proliferative diseases suggest that apoptosis is associated with improvement in the disease.…”
Section: Discussionmentioning
confidence: 87%
“…XAF1 is a negative regulator of XIAP, upregulating apoptosis by antagonizing the anti-caspase activity of XIAP [21]. XAF1 also antagonizes the cellular inhibitor of apoptosis genes C-IAP1 and C-IAP2 [22], and may sensitize cells to Fas-mediated apoptosis [23], which is thought to play a role in sarcoidosis [24], [25]. In IHC expression studies, we observed lack of XAF1 expression in sarcoidosis affected tissues and higher XIAP expression within sarcoid granulomas than in surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al [10] observed the presence of increased apoptotic signaling receptors in BALF macrophages (increased expression of Fas receptor and tumor necrosis factor receptor 1) in patients with active sarcoidosis. Shikuwa et al [23] found high concentrations of soluble Fas ligand in BALF of patients with pulmonary sarcoidosis. On the other hand, Stridh et al [24] found that BALF lymphocytes from patients with active sarcoidosis display a nonapoptotic morphology associated with endogenous caspase 3 activity.…”
Section: Discussionmentioning
confidence: 99%